Strategic synergy (London : International Thomson Business, 1998)
This book is about: What is synergy?; Identifying opportunities; Creating synergy benefits; Synergy in practice; ...
Keywords: Business; Management; Corporations; Strategic planning; Strategic planning; Conglomerate corporations -- Management